(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: Colorectal cancer is a disease in which cells in the colon or rectum grow out of control. Colorectal carcinoma is one of the most frequent malignancy in the world. The purpose of the present study was to see the demographic and clinicopathological patterns of colorectal cancer among patients attended at a tertiary care hospital of Chattogram. Materials and methods: The study was a retrospective, single centre, observational type, carried out in the Department of Medical Oncology & Radiotherapy of Chattagram Maa Shishu-O-General Hospital. Baseline data were collected in a semi structured questionnaire and all reports were documented from pathology or from medical record departments. Results: A total of 70 cases of colorectal cancer patient’s ages ranges from 16 to 73 years where 30% of the patients were within 46-55 years and both sexes were included in the study. Majority of them were male 44 (62.85%) and from rural area (60%). 50% of patients were from the middle class group. Among all 70 cases, rectal site was in 37 (52.85%) patients and most of the patients 44 (62.85%) were histopathologically found in stage IV. Among 70 cases Immunohistochemistry (IHC) was done only 14.28% and histopathological types of colorectal carcinoma showed majority adenocarcinomas 90%. Conclusion: In conclusion, middle-aged and middle-class male patients are most vulnerable to colorectal cancer, and most of them are diagnosed at stage IV. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 73-77